Creating, Metavoicing, and Propagating: A Road Map for Understanding User Roles in Computational Advertising. Issue 4 (7th August 2020) - Liu-Thompkins, Yuping; Maslowska, Ewa; Ren, Yuqing; Kim, Hyejin
Abstract: Over the past two decades, everyday users have become a prominent force in the advertising landscape. They actively participate in conversations with and about brands by creating, amplifying, and interacting with brand-related messages. These user activities generate large volumes of structured and unstructured data that advertisers can mine to understand consumer interests and preferences. In this article, we survey insights from the user-generated content literature through the computational advertising lens to offer a road map for future research. Specifically, we discuss three roles that users play—as creators, metavoicers, and propagators. For each role, we present key research areas that can benefit from a computational approach, identify the opportunities and challenges, and propose questions for future research. We also discuss the practical implications of applying computational methods to study users and user-generated content for advertisers.